Physical game demands in elite Rugby Union: A global positioning system analysis and possible implications for rehabilitation - Coughlan, G. F.; Green, B. S.; Pook, P. T.; Toolan, E.; O'Connor, S. P. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Descriptive. OBJECTIVES: To evaluate the physical demands of an international Rugby Union-level game using a global positioning system (GPS). BACKGROUND: Elite Rugby Union teams currently employ the latest technology to monitor and evaluate physical demands of training and games on their players. METHODS: GPS data from 2 players, a back and a forward, were collected during an international Rugby Union game. Locomotion speed, total body load, and body load sustained in tackles and scrums were analyzed. RESULTS: Players completed an average distance of 6715 m and spent the major portion of the game standing or walking, interspersed with medium- and high-intensity running activities. The back performed a higher number of high-intensity sprints and reached a greater maximal speed. Body load data revealed that high levels of gravitational force are sustained in tackling and scrum tasks. CONCLUSION: The current study provides a detailed GPS analysis of the physical demands of international Rugby Union players. These data, when combined with game video footage, may assist sports medicine professionals in understanding the demands of the game and mechanism of injury, as well as improving injury rehabilitation.